New species and records of Cheiromyia Dyte from Brazil and French Guiana (Diptera: Dolichopodidae) - Brooks, Scott E.; Cumming, Jeffrey M.; Limeira-De-Oliveira, Francisco; Pollet, Marc (Zootaxa, 2018)
Cheiromyia carolina Limeira-de-Oliveira & Brooks sp. nov. and C. nordestina Limeira-de-Oliveira & Cumming sp. nov. are described from Brazil, and C. fuscipennis Pollet & Brooks sp. nov. is described from the Mitaraka Mountains in southwestern French Guiana. New distribution records are reported for C. brevitarsis Brooks, C. palmaticornis (Parent) and C. pennaticornis (Parent), and a revised key to males of the eight known species of Cheiromyia Dyte, 1980 is provided. The female of C. pennaticornis is also described for the first time.